Farmers’ Awareness and Satisfaction related to Insurance products - A study in Nalgonda District - Nazia Sultana, Sri Nikhila, (European Economic Letters (EEL), 2024)
The broad objective of the study is to investigate farmers awareness on insurance products in Nalgonda District. As a part of the investigation 450 farmers were surveyed during June-Dec 2023 data has been analysed using chi-square, ANOVA and descriptives. It was observed that farmers tend to possess more knowledge on crop and livestock insurance compared to life, automobile and property insurance. It is also found that educational qualifications and farming methods have an impact on awareness on insurance products. It is found that, there is a significant difference between the groups, indicates that participants policy renewal behaviour and redressal method are influenced. It is found that there are diverse barriers to crop insurance uptake such as low awareness and interest, confidence issues, procedural complexities, lack of support. It is found that not opting for livestock insurance, farmers have lack of trust in insurance companies, inability to pay the premium as there are financial burdens and the farmers feel it as tedious and time-consuming. It is found that farmers are satisfied with the guidance and assistance provided by insurance specialists, as well as the prompt field visits conducted to assess losses. However, there are concerns regarding the outdated methods utilized for assessing crop loss, occasionally resulting in inadequate and delayed payments as seen in the case of livestock farmers where there was a delayed response to cattle deaths and delays in receiving insurance claim payments for insured animals.